Human disease caused by Streptococcus alactolyticus: a case report of native valve infective endocarditis and review of the literature - Mylonas, Charalampos Chrysanthos; Gomatou, Georgia; Poulakou, Garyphallia; Moraitou, Eleni; Syrigos, Konstantinos (Monaldi Archives for Chest Disease, 2020)
Streptococcus alactolyticus, a member of the Streptococcus bovis/Streptoccus equinus complex, is primarily hosted in the gastrointestinal tract of animals and rarely of humans, with only scarce reports relating to human disease. We herein present a case of subacute infective endocarditis (IE) caused by S. alactolyticus in a 64-year old male with pre-existing mitral prolapse. Despite a 10-month history of low-grade fever and weight loss, the diagnosis of IE was triggered by left quadrant abdominal pain which revealed splenic infarcts on computed tomography. A definitive diagnosis of IE was subsequently established by four consecutive blood cultures positive for S.alactolyticus plus demonstration of a vegetation on the mitral valve by trans-esophageal ultrasound. Further workup revealed multiple embolic phenomena including brain and spine. A dental abscess was identified as the most probable origin of the bacteraemia, while colonoscopy revealed no evidence of cancer. The patient recovered uneventfully with antibiotic treatment and underwent successful cardiac surgery post-discharge. Although rare, IE caused by S. alactolyticus may be severe and of obscure origin; oral cavity should not be overlooked as a possible origin. Attention should be given in patients with preexisting risk factors.